KEHIDUPAN SOSIAL DAN INTERAKSI ORANG DENGAN HIV-AIDS DI YOGYAKARTA - Listiana Listiana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
Stigma about HIV-AIDS disease that leads to PLWHA (PeopleLiving with HIV/AIDS), made its own challenges in conductingsocial processes include interaction. Interaction in society not only as in interactions with others, but with family and community is also becoming a force on for PLWHA (People Living with HIV/AIDS) to continue his social life can make. PLWHA (People Living with HIV/ AIDS) shows open attitude in conducting community interaction, though their hearts are always overshadowed by the negative stigma that will lead to them if the community knows it. Concealment of identity and the intermingling of words disguises them in communitygroups is their interaction strategies in strengthening of the existence in the society. The use of symbols in the form of words disguises is valid only for the person who already knows the circumstances of PLWHA (People Living with HIV/AIDS). The disguise of words will not apply when PLWHA (People Living with HIV/AIDS) are dealing directly with the public. Common symbols in society will apply to groups of PLWHA (People Living with HIV/AIDS) as well as when interacting with the community, but the meaning of these symbols will be different when they interact with other PLWHA (People Living with HIV/AIDS) and people who already know it.